The prevalence of contraceptive use among postpartum women and its associated factors during the early phase of COVID-19 outbreak: a time series study - Sarochinee Sathitloetsakun; Phanupong Phutrakool; Duangporn Maitreechit; Somsook Santibenchakul; Unnop Jaisamrarn; Pimpitcha Puangsricharoen (BMC, 2024)
Abstract Background Unintended pregnancies can adversely affect maternal health, preventable through timely postpartum contraception. During the COVID-19 pandemic, family planning services were constrained by policies that curtailed outpatient visits. We investigated the prevalence of postpartum contraceptive initiation at King Chulalongkorn Memorial Hospital (KCMH) during January to June 2020, comparing with the same period in 2019, and identified factors associated with such initiation. Methods We reviewed the medical records of 4506 postpartum women who delivered at KCMH during the study period. Logistic regression was conducted to test the association between early COVID-19 phase deliveries and post-partum long acting reversible contraception (LARC) initiation including copper intrauterine devices, levonorgestrel intrauterine systems, contraceptive implants, and progestogen-only injectable contraceptives. Results A total of 3765 women (83.6%), of whom 1821 delivered during the pandemic and 1944 during the historical cohort period, were included in this study. The proportion of women who initiated non-permanent modern contraceptives at six weeks postpartum was comparable between the COVID-19 (73.4%) and historical cohort (75.3%) (p = 0.27) periods. The proportion of women who initiated LARC at six weeks postpartumwas comparable between the historical cohort period (22.5%) and the COVID-19 (19.7%) (p = 0.05) period. Accessing a six-week postpartum check-up was independently associated with LARC initiation, of which the adjusted odds ratio (OR) (95% confidence interval) was 3.01 (2.26 to 4.02). Conclusions Our findings demonstrated that accessing postpartum care significantly associate with the use of LARC. The data suggest the strong influence of postpartum check-ups in facilitating the adoption of effective contraception, emphasizing the need for accessible postpartum care to sustain maternal health during health crises.